Ricoeur's ethics of the person, complemented by Aquinas's analogy, developed as an intercultural hermeneutic - Daughton, Amy (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2011)
This summary is intended to provide a succinct overview of the methods used and the major findings of this thesis. I will begin by presenting my methodology before indicating the final conclusions of this work. The primary intellectual dialogue noted in the title, between Paul Ricoeur and Thomas Aquinas, is a largely new endeavour. I am using Aquinas's understanding of the difficulty of speaking of God to think about the particular problem of intercultural encounters in the context of Ricoeur’s ethics. While there has been dialogue more broadly between philosophy and theology in the light of Ricoeur's work, the specific contribution of Aquinas on analogical language has not been developed. I therefore respond to Ricoeur's own commentary on analogy in four broad stages. Firstly, by reconstructing the important context of the concept of the person and the ethical framework of self, other, and just institution, which Ricoeur builds upon that concept. Secondly, by reconstructing Ricoeur's direct work on Aquinas and juxtaposing it with the contribution of other modem commentators, providing an alternative view. Thirdly, I map the changing view of Ricoeur on the usefulness of analogical language as a theological response to the biblical text, and in terms of his work on historiography. Fourthly and finally, I place this analysis in the context of Ricoeur's writing on intercultural encounters.
Keywords: Religion & Theology, Ph.D.; Ph.D. Trinity College Dublin.